Ideological Topoi And Discursive Strategies In Ayman Al-Zawahiri’s And Abu Bakr Al-Baghdadi’s Jihadi Speeches: A Critical Discourse Analysis - Al-Rikaby, Ali Badeen Mohammed (2018)
This study on the use of discursive strategies and ideological topoi as reflected in the political speeches of al-Qa’ida’s leader, Ayman al-Zawahiri and ISIS leader, Abu Bakr al-Baghdadi, drawing on different historical-political perspectives, is the result of a particular interest in the ways rhetorical and figurative language is employed in jihadi politics. Since the rise of the two radical movements as an outcome of the convulsions of the war in Iraq (2003-2011), the Arab revolutions (2010-present) and the civil war in Syria (2011-present), the increasing power of the non-state leaders makes it crucial to study their political speeches, to identify their jihadi discourse topics, their discursive strategies, topoi, fallacies and their micro-legitimatory tools. The study approaches al-Qa’ida and ISIS jihadi rhetoric from a multidisciplinary discourse-analytical perspective to deepen our understanding of the two movements’ political power and rhetoric. To achieve this aim, five speeches for each of the two non-state leaders are analyzed with methodological tools provided by Reisigl’s and Wodak’s (2001; 2009) discourse-historical approach and van Dijk’s (1998) ideological square. The extensive analyses of the discourse topics in the jihadi rhetoric of al- Zawahiri and al-Baghdadi designate that the legitimisation of ‘Self’ is basically tailored via constructing and de- legitimising the ‘Other’ as evil and as a forthcoming threat. Even though religious authority is treated with respect and appreciated as a sign of veneration, it is employed as a source of referential, predication and argumentation for violent acts. The study concludes that the progress of both non-state leaders in capturing widespread support for extremism among Muslims via their rhetorical tactics is inextricably linked to the enormous degrees of alienation that distance many Arab youths from their own local governments in particular and from their Western sponsors in general, and thus, making their arguments both political and ideological.